An Investigation of Urban Equipment Design in the Historical Environment based on Hagia Sophia - Sultan Ahmed Square Example - Uzgör, Onur; Sirel, Ayse; Yücel Caymaz, Gökçen Firdevs (Street Art & Urban Creativity, 2022)
Historical environment requires a respectful act of conservation with a view to sustain cultural heritage. The increasing trend of continuous change in cities is associated with emergent requirements in physical, economic, and socio-cultural fields. There is an ongoing quest for solutions in the fields of architecture and urban planning aimed to accommodate the ever-changing conditions. Nevertheless, despite the projects at city and building scale, the same are uncontrolled or inadequate at the detail scale. Therefore, approaches adopted in the industrial product design level may fall outside the scope of the conservation project in historical environments. The use of urban furniture is required in the public squares in historical environments. However, these products may be in disharmony with their historical environment and have an appearance that harms the urban culture. In case negligent installation techniques are used for the equipment element, this may lead to destruction of the historical environment and hinder the sustainability of cultural values. The "urban equipment element" term was adopted for the general definition of the objects, products, elements, equipment, units, and modules investigated within the scope of the study. The present article aimed to investigate the criteria that could ensure that urban equipment elements were in harmony with the historical environment and help with conserving cultural heritage. The design and classification criteria of urban equipment elements were investigated within the framework of the integrity and harmony of the historical city. For the purposes of the field study, the criteria associated with the functional type, user type, assembly technique, duration of use, infrastructure use along with visual relationship (form-color-tissue-material) in interaction with historical environment, and experiential relationship with environment in the scope of the historical vicinity of Hagia Sophia and Sultan Ahmed Square were analyzed. It was concluded as a result of the that urban equipment elements in historical environments should be designed in an original appearance in harmony with cultural heritage in relation to each other; thus, cultural sharing and transfer might also benefit from experiential relationship with the historical environment; and furthermore, combining multiple functions in urban equipment elements would eliminate visual chaos in the historical environment, contributing to visual harmony.